TOMAMAEITE Cu3 Pt IN NATIVE OSMIUM FROM RIVER SEDIMENTS IN THE NIZHNIE SERGI REGION, CENTRAL URALS - V.V. Sharygin; I.G. Mikhailov (Минералогия)
The article is devoted to tomamaeite Cu3 Pt from inclusions in a native osmium grain from alluvial river sediments in the Nizhnie Sergi region, Sverdlovsk oblast. It is the fourth finding of this mineral in the Urals. In addition to tomamaeite, native osmium Os0.36Ir0.33Ru0.31 contains the inclusions of digenite (or, possibly, roxbyite), millerite, Fe-Ni-Pt alloy, an unidentified Pd mineral, magnesiohornblendite, and lowCa pyroxene. In composition, tomamaeite is close to the ideal formula Cu3 Pt and contains minor amounts of (wt. %) Pd (up to 2.0), Ir (up to 1.7), Ru and Ni (up to 0.6), and Fe (up to 0.2). In addition to native osmium, two grains of native ruthenium Ru0.54Os0.23Ir0.23 and Ru0.40Os0.31Ir0.29 are found in sediments. Our data suggest that the PGE minerals in river sediments could be sourced from mafic-ultramafic massifs located in the Nizhnie Sergi area. The formation of tomamaeite and coexisted minerals is related to the process of postmagmatic transformation of the primary PGE mineral assemblage, probably, during serpentinization of ultramafic rocks.